The Effect of Corporate Culture and Innovation on Employee Performance, with Knowledge Sharing as sn Intervening Variable, at Bank BJB - Dwiputrana, Hatta Zul Khamisa; Hayati , Neneng (Journal Research of Social Science, Economics, and Management, 2026)
This research is motivated by the demands of digital transformation in the banking sector, which require an adaptive, innovative, and collaborative work culture to enhance sustainable employee performance. Although Bank BJB has shown improvement during 2022–2024, challenges remain, including uneven cultural implementation, low employee participation, and limited knowledge sharing. This research aims to analyze the influence of organizational culture and innovation on employee performance with knowledge sharing as an intervening variable in Bank BJB.. This study uses a quantitative approach with causal design to examine the cause-and-effect relationship between organizational culture (X1) and innovation (X2) variables on employee performance (Y), either directly or indirectly through knowledge sharing (Z). The data analysis technique uses multiple linear regression to test the direct influence and mediation between variables. The results of the study are expected to show that organizational culture and innovation have a positive and significant influence on employee performance, both directly and through knowledge sharing as an intervening variable. Knowledge sharing plays an important role in strengthening the relationship between organizational culture and innovation on employee performance, thereby creating a productive, adaptive, and learning-oriented work environment. The implications of this study provide recommendations for the management of Bank BJB to strengthen an adaptive organizational culture, improve the innovation ecosystem, and optimize a digital-based knowledge sharing system to support the improvement of employee performance and company competitiveness in the digital era.